Subfoveal choroidal thickness after photodynamic therapy in patients with acute idiopathic central serous chorioretinopathy - Dang Y; Sun X; Xu Y; Mu Y; Zhao M; Zhao J; Zhu Y; Zhang C (Dove Medical Press, 2014)
Yalong Dang,1–3,# Xinfeng Sun,2,# Yongsheng Xu,3,# Yalin Mu,2 Manli Zhao,2 Jing Zhao,2 Yu Zhu,1 Chun Zhang31Department of Ophthalmology, First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province, 2Department of Ophthalmology, Yellow River Hospital, Henan University of Science and Technology, Sanmenxia, Henan Province, 3Clinical Stem Cell Research Center, Peking University Third Hospital, Beijing, People's Republic of China #These authors contributed equally to this work Background: The purpose of this study was to evaluate changes in subfoveal choroidal thickness after photodynamic therapy in patients with acute idiopathic central serous chorioretinopathy (ICSCR). Methods: This was a retrospective observational study conducted in 63 participants. The primary outcome measure was subfoveal choroidal thickness at baseline and 3 days, one week, 4 weeks, and 12 weeks after photodynamic therapy. The secondary outcome measure was indocyanine green angiography at baseline and 4 weeks and 12 weeks after photodynamic therapy. Results: Four weeks after photodynamic therapy, 20 (64.51%) symptomatic eyes showed hypofluorescence corresponding to the area of photodynamic therapy irradiation at the posterior pole. The mean subfoveal choroidal thickness increased significantly from 422±132 µm at baseline to 478±163 µm at day 3 after treatment (P=0.022) and then decreased to 362±113 µm at week 4 (P<0.001) and 339±135 µm at week 12 (P<0.001). Conclusion: The subfoveal choroid in patients with acute ICSCR is thicker than in the normal population, and in symptomatic eyes is significantly thicker than in fellow eyes. Photodynamic therapy using a one third dose of verteporfin may decrease choroidal vascular hyperpermeability and choroidal thickness in patients with acute ICSCR. Keywords: idiopathic central serous chorioretinopathy, photodynamic therapy, subfoveal choroidal thickness, indocyanine green angiography, optical coherence tomography, enhanced depth imaging